Integrated phosphorus nutrient sources improve wheat yield and phosphorus use efficiency under sub humid conditions. - Khuram Mubeen (Public Library of Science (PLoS), 2021)
Majority of Pakistani soils are deficient in phosphorus. Phosphorus is usually applied in form of synthetic fertilizer. However integrated use of P from synthetic and organic sources can be more profitable and beneficial on sustainable basis. Field trials were conducted at research farm University of Poonch, Rawalakot, AJK, Pakistan for two consecutive years to check the comparative effects of synthetic fertilizer and organic manures applied alone and in combinations on the phosphorus use efficiency (PUE), wheat yield and yield components. Shafaq-06 cultivar of wheat was used as test cultivar. Ten treatments were included: (I) Control (P0) without application of fertilizer; (II) SSP @ 60 kg/ha (P60SSP); (III) SSP @ 90 kg/ha (P90SSP); (IV) SSP @ 120 kg/ha (P120SSP); (V) PM @60 kg/ha (P60PM); (VI) PM @90 kg/ha (P90PM); (VII) PM @120 kg/ha (P120PM); (VIII) SSP @30 kg/ha + PM @30 kg/ha (P30SSP+30PM); (IX) SSP @45 kg/ha + PM @45 kg/ha (P45SSP+45PM); (X) SSP @60 kg/ha + PM @60 kg/ha (P60SSP+60PM) which were laid out under the Randomized Complete Block Design. Significantly higher values for yield of grain (2397 kg/ha) was recorded with PM + SSP @ 60 kg P2O5 ha-1 each. Likewise, FPUE, PIR of wheat and AFPUE was quite higher with combined use of PM and SSP i.e. P60SSP+60PM treatment. Additionally, increase in PUE, wheat yield and yield components associated with combined treated plot would help to minimize the use of high cost synthetic mineral fertilizers and represents an environmentally and agronomically sound management strategy.